Indonesia Government’s Responses to COVID-19: A Critical Review to Pre-Crisis and Crisis Phase - Setyoningsih Subroto; A A Istri Putri Dwijayanti; Reza Yohanes (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2021)
The COVID-19 pandemic in Indonesia divides society's opinion into 2 sides. The opinion was mostly affected by the government’s responses during the pre-crisis and crisis phase. Therefore, this study aims to review the government’s crisis responses that already appeared. A qualitative method was used to determine the issue. The data are taken from COVID-19 official websites and online news portals portrayed from February until April 2020. From the data resource, the author then found that some mistakes appeared both in the pre-crisis and crisis phase. The mistakes consist of; (1) lack of emergency responses to crucial information, (2) inappropriate key messages, (3) inconsistent statements from the government, (4) the changing of spokesperson Furthermore, the author provides several recommendations to the Indonesian government for the proper response during the pre-crisis and crisis-phase for the other issue in the future. The recommendations are; (1) being consistent in every information that delivers to society, (2) avoid controversial statements, (3) form a communication task force team to develop and convey the message.Keywords: crisis communication, Indonesia, COVID-19